Investigating the discharge characteristics over a piano key weir with varying key slope and key width ratios under varying discharges - Iqbal Mujahid; Ghani Usman (Journal of Hydrology and Hydromechanics, 2025)
The objective of the present study was to investigate the effect of inlet to outlet key slope ratios (Si/So), inlet to outlet key width ratios (Wi/Wo) and head over the weir on the coefficient of discharge (Cpkw) of type-A trapezoidal piano key weir (TPKW). It was observed that the Cpkw of TPKW was found to be decreased as the Si/So ratio reduced. The percentage of reduction in Cpkw was found to be 18.5%, 16%, 13.7%, 9.4%, 6.3%, and 3% at Si/So = 0.60, 0.75, 0.80, 1.00, 1.25, and 1.33, respectively in comparison with the Si/So = 1.67. As far as the effect of Wi/Wo ratio on the Cpkw of TPKW is concerned, the Cpkw of TPKW was observed to be increased with increasing Wi/Wo ratios. Moreover, the Cpkw at Wi/Wo = 1.32 and Wi/Wo = 1.15 was found to be 9.4% and 7.5% higher than Wi/Wo=1 respectively, while for the case of Wi/Wo = 0.76, its value was found to be 3.3% lower than Wi/Wo = 1. Furthermore, the hydraulic efficiency of TPKW was found to be decreased as head over the weir increased. The maximum value of Cpkw of TPKW was observed to be 3.2 corresponding to lowest h/P ratio for the model having Si/So = 1.67 and Wi/Wo = 1.32, while the minimum value of Cpkw of TPKW was found to be 1.58 corresponding to highest h/P ratio for the model having Si/So = 0.60 and Wi/Wo = 0.76. Additionally, sensitivity analysis results revealed that the Cpkw of TPKW is more sensitive with h/P ratio than other ratios.